Family Businesses and Traditional Crafts: Heritage, Continuity, and Innovation - Tomášková, Andrea (Publishing House of Wroclaw University of Economics and Business, 2025)
Traditional crafts form a significant part of cultural heritage and contribute to cultural, economic, and social sustainability, yet they face threats due to the decline in bearers of tradition and insufficient intergenerational transmission. Local communities and small family businesses play a key role in preserving and developing crafts. The author focused on the Hlinecko microregion and analysed case studies in order to demonstrate how the combination of tradition, innovation, and entrepreneurship within a family environment supports intergenerational exchange and cultural sustainability. The analysis showed that traditional crafts can find new forms of application in the current social and economic context.
Quote as: Tomášková, A. (2025). Family Businesses and Traditional Crafts: Heritage, Continuity, and Innovation. In B. Drelich-Skulska, M. Sobocińska, & A. Tomášková (Eds.), Sustainable Development in Light of Research by Scientists from Poland, Czechia and Slovakia. Different Research Perspectives (pp. 217-226). Publishing House of Wroclaw University of Economics and Business.
Keywords: crafts; cultural heritage; intergenerational exchange; sustainable development